Auditor's Ability to Detect Fraud Through Competence, Independence, Integrity and Professionalism - Basmar, Nur Azizah; Rinaldy, Syiar; Sahidah, Sahidah (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to analyze the influence of competence, independence, integrity and professionalism on the ability of internal auditors to detect fraud. The type of research in this research is quantitative. The population in this study were all auditors at the Makassar City Inspectorate Office. Data provided by the Inspectorate was 35 auditors (source: Makassar City Inspectorate Performance Report). The sampling method used in this research is the saturated sample method. The saturated sampling method is a sampling technique when all members of the population are used as samples. By using multiple linear regression analysis and hypothesis testing. The research results found that competence has a positive and significant effect on the ability of internal auditors to detect fraud; independence has a positive and significant effect on the ability of internal auditors to detect fraud; integrity has a positive and significant effect on the ability of internal auditors to detect fraud; professionalism has a positive and significant effect on the ability of internal auditors to detect fraud.